Construction and preliminary immunobiological characterization of a novel, non-reverting, intranasal live attenuated whooping cough vaccine candidate - Cornford-Nairn, R.; Daggard, G.; Mukkur, Trilochan (Han'gug Mi'saengmul Saengmyeong Gong Haghoe, 2012)
We describe the construction and immunobiological properties of a novel whooping cough vaccine candidate, in which the aroQ gene, encoding 3-dehydroquinase, wasdeleted by insertional inactivation using the kanamycin resistance gene cassette and allelic exchange using a Bordetella suicide vector. The aroQ B. pertussis mutant required supplementation of media to grow but failed to grow on an unsupplemented medium. The aroQ B. pertussis mutant was undetectable in the trachea and lungs of mice at days 6 and 12 post-infection, respectively. Antigen-specific antibody isotypes IgG1 and IgG2a, were produced, and cell-mediated immunity [CMI], using interleukin-2 and interferon-gamma as indirect indicators, was induced in mice vaccinated with the aroQ B. pertussis vaccine candidate, which were substantially enhanced upon second exposure to virulent B. pertussis. Interleukin-12 was also produced in the aroQ B. pertussis-vaccinated mice. On the other hand, neither IgG2a nor CMI-indicator cytokines were produced in DTaP-vaccinated mice, although the CMI-indicator cytokines became detectable post-challenge with virulent B. pertussis. Intranasal immunization with one dose of the aroQ B. pertussis mutant protected vaccinated mice against an intranasal challenge infection, with no pathogen being detected in the lungs of immunized mice by day 7 post-challenge. B. pertussis aroQ thus constitutes a safe, non-reverting, metabolite-deficient vaccine candidate that induces both humoral and cellmediated immune responses with potential for use as a single-dose vaccine in adolescents and adults, in the first instance, with a view to disrupting the transmission cycle of whooping cough to infants and the community.